Nanoscale origins of super-capacitance phenomena - Bueno, Paulo R. [UNESP] (Elsevier, 2019)
We review the origins of capacitive phenomena at the nanoscale to demonstrate that electrochemistry cannot be understood without a critical re-reading of nanoscale electronics, and vice-versa. The fundamentals are stated at a mesoscopic physical level at which both classical and quantum mechanical terms are important to the explanation of different capacitive contributions. At this mesoscopic physical scale, a quantum mechanical Hamiltonian can be analytically solved for a metal-electrolyte interface modified with an ensemble of molecular-scale building blocks. This mesoscopic electrochemical state arises in most situations involving nanostructured electrochemical junctions, while the outcome of resolving the Hamiltonian associated with this mesoscopic problem is electrochemical capacitance. Therefore, in the present study, we departed from the conventional meaning of electrochemical capacitance to demonstrate that non-faradaic and faradaic charging events are identical phenomena. Using specific examples in which these approximations apply, we elucidate and generalize the common molecular origin of double-layer and pseudo-capacitive charging phenomena. This important fundamental knowledge obviously impacts the development of nanostructured super-capacitors, researchable batteries, etc. Additionally, we discuss the principle of operation of non-faradaic and faradaic capacitive sensing devices, which are notable for conforming to equivalent principles. In summary, super-capacitance phenomena are introduced and elucidated from first-principles quantum mechanics outcomes.
Keywords: Batteries; Capacitive biosensors; Debye–Hückel; Electrical field screening; Molecular electrochemistry; Nanoscale electrochemistry; Nanoscale energy-storage principles; Nanostructures; Power source; Pseudo-capacitors; Quantum electrochemistry pseudo-capacitors; Super-capacitors; Thomas–fermi